Increasing atmospheric CO2 differentially supports arsenite stress mitigating impact of arbuscular mycorrhizal fungi in wheat and soybean plants. (June 2022) - AbdElgawad, Hamada; El-Sawah, Ahmed M.; Mohammed, Afrah E.; Alotaibi, Modhi O.; Yehia, Ramy S.; Selim, Samy; Saleh, Ahmed M.; Beemster, Gerrit T.S.; Sheteiwy, Mohamed S.
Abstract: Arbuscular mycorrhizal fungi (AMF) are beneficial for the plant growth under heavy metal stress. Such beneficial effect is improved by elevated CO2 (eCO2 ). However, the mechanisms by which eCO2 improves AMF symbiotic associations under arsenite (As III ) toxicity are hardly studied. Herein, we compared these regulatory mechanisms in species from two agronomical important plant families – grasses (wheat) and legumes (soybean). As III decreased plant growth (i.e., 53.75 and 60.29% of wheat and soybean, respectively) and photosynthesis. It also increased photorespiration and oxidative injury in both species, but soybean was more sensitive to oxidative stress as indicated by higher H2 O2 accumulation and oxidation of protein and lipid. eCO2 significantly improved AMF colonization by increasing auxin levels, which induced high carotenoid cleavage dioxygenase (CCDs) activity, particularly in soybean roots. The improved sugar metabolism in plant shoots by co-application of eCO2 and As III allocated more sugars to roots sequentially. Sugar accumulation in plant roots is further induced by AMF, resulting in more C skeletons to produce organic acids, which are effectively exudated into the soil to reduce As III uptake. Exposure to eCO2 reduced oxidative damage and this mitigation was stronger in soybean. This could be attributed to a greater reduction in photorespiration as well as a stronger antioxidant and detoxification defence systems. The grass/legume-specificity was supported by principal component analysis, which revealed that soybean was more affected by As III stress and more responsive to AMF and eCO2 . This study provided a mechanistic understanding of the impact of AMF, eCO2 and their interaction on As-stressed grass and legume plants, allowing better practical strategies to mitigate As III phytotoxicity. Graphical abstract: Image 1 Highlights: Soybean was more sensitive to As stress but more reponsive to AMF and eCO2 impact. High strigolactone biosynthesis by eCO2 induced AMF colonization, mainly in soybean. Increased photosynthesis by eCO2 allocated more sugars to AMF roots of soybean and wheat. eCO2 increased soil retention resulting in less As accumulation in AMF treated plants. eCO2 strengthen AMF impact on decreasing ROS production and increasing their detoxification.